Piezol and BKca channels in human atrial fibroblasts: Interplay and remodelling in atrial fibrillation - Jakob, Dorothee; Klesen, Alexander; Allegrini, Benoit; Darkow, Elisa; Aria, Diana; Emig, Ramona; Chica, Ana Simon; Rog-Zielinska, Eva A.; Guth, Tim; Beyersdorf, Friedhelm; Kari, Fabian A.; Proksch, Susanne; et al. (Journal of molecular and cellular cardiology, 2021)
Aims: Atrial Fibrillation (AF) is an arrhythmia of increasing prevalence in the aging populations of developed countries. One of the important indicators of AF is sustained atrial dilatation, highlighting the importance of mechanical overload in the pathophysiology of AF. The mechanisms by which atrial cells, including fibroblasts, sense and react to changing mechanical forces, are not fully elucidated. Here, we characterise stretch-activated ion channels (SAC) in human atrial fibroblasts and changes in SAC- presence and activity associated with AF. Methods and results: Using primary cultures of human atrial fibroblasts, isolated from patients in sinus rhythm or sustained AF, we combine electrophysiological, molecular and pharmacological tools to identify SAC. Two electrophysiological SAC- signatures were detected, indicative of cation-nonselective and potassium-selective channels. Using siRNA-mediated knockdown, we identified the cation-nonselective SAC as Piezol. Biophysical properties of the potassium-selective channel, its sensitivity to calcium, paxilline or iberiotoxin (blockers), and N511021 (activator), indicated presence of calcium-dependent 'big potassium channels' (BKca). In cells from AF patients, Piezol activity and mRNA expression levels were higher than in cells from sinus rhythm patients, while BKca activity (but not expression) was downregulated. Both Piezol-knockdown and removal of extracellular calcium from the patch pipette resulted in a significant reduction of BKca current during stretch. No co-immunoprecipitation of Piezol and BKca was detected. Conclusions: Human atrial fibroblasts contain at least two types of ion channels that are activated during stretch: Piezol and BKca. While Piezol is directly stretch-activated, the increase in BKca activity during mechanical stimulation appears to be mainly secondary to calcium influx via SAC such as Piezol. During sustained AF, Piezol is increased, while BKca activity is reduced, highlighting differential regulation of both channels. Our data support the presence and interplay of Piezol and BKca in human atrial fibroblasts in the absence of physical links between the two channel proteins.
Im Titel sind die Zeichen "ca" tiefgestellt
Gesehen am 09.12.2021